Duty Bearers and Care Seekers (Journal of Nobel Medical College, 2023)
Health care systems and businesses have a common format of service delivery to the customer. Both internal and external customers are there and the difference is in the urgency, degree of continuity of care, and sensitivity of issues. Motivation of internal customers and satisfaction of external customers are the key elements of success. The service system is described as a Four-block service system.